Celecoxib has Preventive and Therapeutic Benefits against Nephrotoxicity Caused by Gentamicin in Mice - Abd-Eldayem, Ahmed M.; Dahpy, Marwa A.; Badary, Dalia M.; Alnasser, Sulaiman Mohammed; Hareedy, Mohammad Salem (Drug Research, 2022)
It’s crucial to comprehend the impact of oxidative stress and pro-inflammatory cytokines in the gentamicin-induced kidney injury mechanism. Celecoxib was administered orally either before or after intraperitoneal therapy with gentamicin in mice. The serum levels of creatinine (SCr), blood urea nitrogen (BUN), IL-6, and TNF-α were measured by ELISA test, as well as the levels of the kidney tissue malondialdehyde (MDA), and glutathione (GSH) were also estimated spectrophotometrically. The renal expression of nuclear factor-κB (NF-κB), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and cyclooxygenase 2 (COX-2) mRNAs were evaluated by qPCR. Histopathological evaluation and Immunohistochemical examination of kidney NF-κB, IL-6, and COX-2 were also, performed. Celecoxib successfully prevented gentamicin-induced kidney damage as indicated by reducing blood BUN, SCr, and tissue MDA levels and increasing renal tissue GSH levels as well as lowering the blood IL-6 and TNF-α in comparison to mice received gentamicin. Furthermore, celecoxib has inhibited COX-2, NF-κB, IL-6, and TNF-α expression in the renal tissue. It is noteworthy that celecoxib therapy after gentamicin administration brought about substantially the same results as celecoxib treatment before gentamicin injection in mice. Our results showed the role of celecoxib as a therapeutic tool for gentamicin-induced nephrotoxicity as well as raised its beneficial prophylactic role in this medical challenge by attenuating oxidative stress and inflammation.
Keywords: Celecoxib; Gentamicin; Nephrotoxicity; Oxidative stress; Inflammatory markers; Mice.